2017
DOI: 10.24215/23142561e037
|View full text |Cite
|
Sign up to set email alerts
|

Incentive of Psychosocial Components In The Trajectory Of Volleyball Athletes

Abstract: Objetivo: Comparar o incentivo dos componentes psicossociais nas diferentes fases da trajetória esportiva em atletas de voleibol nas categorias de formação. Métodos: Aplicou-se um questionário específico baseado nos elementos dinâmicos da formação esportiva (Côté, 1999; Côté, Turnnidge, & Vierimaa, 2016) em 78 atletas do sexo masculino com média de idade de 19.24±0.9 anos de clubes de reconhecimento nacional brasileiro. Utilizou-se o teste qui-quadrado e a regressão logística multinomial para comparar o ní… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 13 publications
0
3
0
Order By: Relevance
“…Instead, the assessment might reflect the student's process. Similar issues are also raised by Mendes et al (2007) in that students sometimes understand their grades as an exclusively quantitative final product. Indeed, it is important to generate grades because they determine classification and rank.…”
Section: Resultsmentioning
confidence: 75%
See 1 more Smart Citation
“…Instead, the assessment might reflect the student's process. Similar issues are also raised by Mendes et al (2007) in that students sometimes understand their grades as an exclusively quantitative final product. Indeed, it is important to generate grades because they determine classification and rank.…”
Section: Resultsmentioning
confidence: 75%
“…Educators have used numerous approaches to investigate student-teachers' assessment experiences. These include debates related to student perceptions of assessment and their implications for teacher interventions (Goc-Karp & Woods, 2008), investigations of the assessment practices experienced by physical education teachers during their graduate programs (Mendes, Nascimento, & Mendes, 2007), and dialogues with students attending initial teacher training programs (Santos & Maximiano, 2013). 1 Our investigation takes a different approach.…”
Section: Introductionmentioning
confidence: 99%
“…In this environment, achieving optimal performance becomes crucial for team success. Previous research had shown that psychological and mental factors play a significant role in reaching peak performance in volleyball athletes (Hesami et al, 2020;Machado et al, 2018;Mendes et al, 2017). Therefore, developing effective methods to optimise the psychological and mental aspects of volleyball athletes can provide significant competitive advantages.…”
Section: Introductionmentioning
confidence: 99%